A Mobile based Automated Visitors Management Application for Enhancing Security in Student Housing - Owoola, Seun Isaac (Journal of Information Systems Research and Practice, 2024)
The security of student housing remains a pressing concern for educational institutions due to increasing incidents of unauthorized access and safety threats. Traditional paper-based visitor management systems are inefficient, prone to errors, and lack real-time data accessibility. This study presents a Mobile-Based Automated Visitor Management Application (AVMA) designed to enhance security in student housing. The AVMA leverages modern mobile technology, integrating visitor registration, and advanced access control to streamline the management of visitor activities. Key features include a user-friendly interface for registering visitors, push notifications, and visitor logs, which enhance communication between residents and housing management. The application is developed using the Flutter framework, Dart programming language, and Google Firebase for backend services, ensuring a secure and scalable solution. Initial testing enhanced user experience, making the AVMA a vital application for safeguarding student accommodations.